Synthesis of Triethylamine‐Bridged Basic Tricationic Ionic Liquids and Evaluation of Their Catalytic Efficiencies for Preparation of Arylidene or Alkylidenemalononitrile. Issue 32 (30th August 2018) - Gogoi, Pinky; Boruah, Kabita; Borah, Ruli
Abstract: Two series of basic triethylamine bridged pyridinium/imidazolium tricationic ionic liquids were synthesized as viscous liquids by ion‐pairing with hydroxide, acetate and imidazolide as basic anions. The characterization of tricationic ionic liquids was done using 1 H and 13 C NMR, FT‐IR, Thermogravimetric analysis (TGA), Hammett basicity EI‐MS and elemental analysis techniques. Thermal stabilities were found within the range of 100–150 °C for these ionic liquids. They acted as efficient recyclable homogeneous catalysts for the representative Knoevenagel condensation of benzaldehyde and malononitrile at room temperature stirring in neat condition for 10–20 min. The catalytic activity of these ILs was found to be slightly different from each other for the model reaction and did not follow the same sequence of their measured Hammett basicity value. Abstract : Two classes of basic tricationic triethylamine bridged pyridinium/imidazolium ionic liquids were prepared as viscous liquids in presence of hydroxide, acetate and imidazolide as basic anions. Their structures were confirmed using ( 1 H and 13 C) Nuclear Magnetic Resonance and Infrared spectroscopy, C H N elemental analysis and Electron Ionization Mass Spectrometry techniques. The thermogravimetric and Hammett basicity studies of the ionic liquids were employed to explore the efficient basic catalysts for synthesis of arylidene/alkylidenemalononitrile derivatives at mild condition.